Implementation Of Spiritual Therapy In Controlling Violent Behavior - Sri Endriyani; Sri Martini; Syindy Yulistia (Universitas Widya Gama Mahakam Samarinda, 2022)
Background : Violent behavior is a response to the stressor faced by someone who is shown by committing violence, to oneself, to others, and to the environment, verbally and non-verbally, aiming to hurt others physically and psychologically, which is indicated by actual behavior of violence. To overcome the recurrence, the patient needs to get treatment, there are implementation strategy in the patient Mr. R, Mr. A and Mr. M at Mitra Mulia Foundation. Methods : This research used descriptive in a case study to explore the implementation of spiritual healing nursing in schizophrenia patients with violent behavior problems at the Mitra Mulia Banyuasin Foundation, South Sumatra. The research subjects to be studied amounted to two patients, namely schizophrenic patients with violent behavior problems. The place of research is Mitra Mulia Banyuasin, South Sumatra. Results : The results showed that the implementation of the implementation strategy in patients with violent behavior who suffered from violent behavior was very helpful in healing the patient Mr. R, Mr. A and Mr. M at Mitra Mulia Foundation from March 11 to March 17, 2022. In carrying out the implementation, the author involves patients directly using standard operating procedures. Conclusion : The patient is able to control violent behavior by implementing the 4 spiritual healing strategies that have been taught by the author. Keywords : Schizophrenia, Violent Behavior.